Structural magnetic imaging study on autism - Teo, Eunice Shu Juan. (2013)
Autism is one of the top 10 mental illnesses. It is how some people are born with. The diagnosis takes place as soon as a child starts to display symptoms of autism. The traditional diagnosis can take a lot of time and subjective as it would be a series of questionnaires and observations. Not only time consuming and subjective but also it could be inaccurate if the patient is too young to answer the questionnaires. Autism if detected early and with proper interventions, can be coped and managed and the patient would have no problems living like a normal person. However, there is no cure for autism, the answer to that is to learn how to manage it.